(untitled) (Eurasian Research Bulletin, 2023)
This article examines the effect of the immunostimulator "Fitovak" on mung bean root system. Three different standards of the immunostimulator "Fitovak" were obtained. From here, the development and formation of the root system was observed on the variant of applying 500 ml/t before pre-sowing and 500 ml/ha using different periods (2–4 true leaves, shading, flowering).